(untitled) (Journal of Geography and Environmental Management, 2016)
The article contains description of objectives in designing technical and functional architecture of the information system, created for the field and laboratory data processing by ecological and demographic projects inspection and radiation monitoring of rural communities the Republic of Kazakhstan. The system development program includes the information-based analysis and geographic information subsystem development.